2010
DOI: 10.3171/2010.8.gks10689
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for dural carotid-cavernous sinus fistulas: Gamma Knife compared with XKnife radiosurgery

Abstract: Object In the modern era, stereotactic radiosurgery is an important part of the multidisciplinary and multimodality approach used to treat dural carotid-cavernous fistulas (DCCFs). Based on the ease of performance of techniques to fuse cerebral angiography studies with MR images or CT scans during the radiosurgical procedure, the Gamma Knife and XKnife are 2 of the most popular radiosurgical instruments for patients with DCCF. In this study, the authors compared the efficacy, neurological results, and complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
2
7
1
Order By: Relevance
“…There are several exciting recent reports of successful use of stereotactic radiosurgery for the treatment of CSDF. Pan et al 24 reported their series of 41 patients treated by stereotactic radiosurgery for CSDF with a 90% obliteration rate. Yang and colleagues25 showed similar results in their cohort of 40 patients treated by stereotactic radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are several exciting recent reports of successful use of stereotactic radiosurgery for the treatment of CSDF. Pan et al 24 reported their series of 41 patients treated by stereotactic radiosurgery for CSDF with a 90% obliteration rate. Yang and colleagues25 showed similar results in their cohort of 40 patients treated by stereotactic radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…The latency period between SRS and complete occlusion is one of the main drawbacks of SRS. Compared with AVMs, DAVFs seem to more promptly react to SRS because the shunt size in DAVFs is smaller than that in AVMs [15,16]. Moreover, slow occlusion of DAVFs may reduce the likelihood of venous hypertension [17].…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%
“…In case of failure of both endovascular and surgical treatments, stereotactic radio surgery (SRS) represents an alternative. However, this treatment has low success rate as the only treatment 28 , especially in case of complex lesions for which targeting of the shunt is difficult 29 . Moreover, SRS is generally inappropriate for lesions presenting with bleeding because during the latency period of IDAVF obliteration, which lasts several months to a year, the rehemorrhage risk remains elevated 10 .…”
Section: Treatmentmentioning
confidence: 99%